Memorial: A Record of Solid and Liquid Foods Absorbed in the Course of the Year 1991 - Mathews, Harry (Petits Propos Culinaires, 2001)
Harry Mathews (d. 2017) was an American writer who lived mainly in France since 1952. He was the only American member of the French group Oulipo (Ouvroir de Littérature Potentielle) which according to the Oxford Companion to Literature in French, sees 'the creation of literature as arising most felicitously from the imposition of constraints of a rigid and sometimes mathematical nature'. Members of the group who will be familiar to subscribers include Raymond Queneau, Georges Perec and Italo Calvino. Harry Mathews wrote novels as well as poetry, criticism and allied non-fiction. In this essay the author provides a record of what he ate during 1991 the idea for which came from an earlier exercise undertaken by his friend Georges Perec. The material is organized by food type.